Comparative Analysis of Probability of Failure Determination Using Weibull Distribution and Generic Failure Frequencies on Heat Exchanger Tube Bundles Based on API 581 - Dharma Gita Surya Prayoga; Dwi Priyanta; Nurhadi Siswantoro (International Journal of Marine Engineering Innovation and Research, 2018)
RBI analysis for heat exchanger tube has been explained by API 581. Two types of PoF determination using statistical data is provided to determine the PoF category. Both Weibull parameter and generic failure frequencies are the methods that will be analysis in this present study. PoF determination using Weibull distribution gives the exponential value of PoF in a certain of time. This method only consider failure modes and the failure rate of heat exchanger tube without considering possible active damage mechanisms in the tube. However PoF determination using generic failure frequencies gives more complex consideration. It considers not only failure and possible active damage mechanism, but also the effect of management system facilities of the heat exchanger on the integrity of the plant.